1998
DOI: 10.1007/s002130050731
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre double-blind comparison of hydroxyzine, buspirone and placebo in patients with generalized anxiety disorder

Abstract: The efficacy of hydroxyzine and buspirone, controlled by placebo, was investigated in a double-blind, parallel group, multicentre study conducted in France and the UK. A total of 244 patients with generalised anxiety disorder in primary care was allocated randomly to treatments with hydroxyzine (12.5 mg morning and mid-day, 25 mg evening), buspirone (5 mg morning and mid-day, 10 mg evening) or placebo (three capsules/day) for 4 weeks, preceded by a 1-week single-blind placebo run-in and followed by 1-week sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 9 publications
2
41
1
2
Order By: Relevance
“…In particular, comparisons between standard drugs for GAD and psychotherapy are lacking. One study found no gains in combining buspirone and CBT (Lader and Scotto 1998); however, the statistical power of this study may have been too low. In another study, the combination of CBT and diazepam was more effective than diazepam alone (Power et al 1990).…”
Section: )(D)contrasting
confidence: 56%
See 2 more Smart Citations
“…In particular, comparisons between standard drugs for GAD and psychotherapy are lacking. One study found no gains in combining buspirone and CBT (Lader and Scotto 1998); however, the statistical power of this study may have been too low. In another study, the combination of CBT and diazepam was more effective than diazepam alone (Power et al 1990).…”
Section: )(D)contrasting
confidence: 56%
“…Efficacy of the antihistamine hydroxyzine was established in a DBPC study (Ferreri et al 1994). In a comparator study, hydroxyzine, but not buspirone, was superior to placebo (Lader and Scotto 1998). In another threearm study, hydroxyzine was compared to placebo and the benzodiazepine bromazepam (Llorca et al 2002).…”
Section: )(D)mentioning
confidence: 99%
See 1 more Smart Citation
“…An anxiolytic action can be linked with 5-HT 2A/2C receptor blockade, but H1 receptor antagonism and 5-HT 3 receptor blockade may also be relevant, as both are implicated in anxiolytic effects (Lader and Scotto 1998;Olivier et al 2000;Harmer et al 2006). The increased response to happy facial expressions seems more likely to be linked to antidepressant effects, and here, changes in noradrenergic neurotransmission, perhaps arising from blockade of presynaptic α 2 -adrenoceptors (Davis and Wilde 1996), might be relevant.…”
Section: Discussionmentioning
confidence: 89%
“…(Llorca& Spadone, 2002;Lader &Scotto, 1998).The antihistamine hydroxyzine appears to have higher anxiolytic efficacy than placebo in controlled studies. Because of the side effects (sedation, anticholinergic effects) , slow onset of action, and lack of efficacy for comorbid disorders, hydroxyzine was not recommended to be used as first-line therapy in some guidelines.…”
Section: Antihistaminesmentioning
confidence: 99%